Primordial magnetic fields in population III star formation: a magnetized resolution study - Prole, Lewis R.; Clark, Paul C.; Klessen, Ralf S.; Glover, Simon; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2022)
Population III (Pop III) stars form in groups due to the fragmentation of primordial gas. While uniform magnetic fields have been shown to support against fragmentation in present-day star formation, it is unclear whether realistic k3/2 primordial fields can have the same effect. We bypass the issues associated with simulating the turbulent dynamo by introducing a saturated magnetic field at equipartition with the velocity field when the central densities reach 10−13 g cm−3. We test a range of sink particle creation densities from 10−10 to 10−8 g cm−3. Within the range tested, the fields did not suppress fragmentation of the gas and hence could not prevent the degree of fragmentation from increasing with increased resolution. The number of sink particles formed and total mass in sink particles was unaffected by the magnetic field across all seed fields and resolutions. The magnetic pressure remained sub-dominant to the gas pressure except in the highest density regions of the simulation box, where it became equal to but never exceeded gas pressure. Our results suggest that the inclusion of magnetic fields in numerical simulations of Pop III star formation is largely unimportant.